Neurotrophic regulation of the phosphorylation of a soluble cytosolic protein in skeletal muscle - Held, IR (J Neurosci, 1983)
Neural influences are exerted not only by propagation of nerve impulses, but also by trophic actions of the motor neuron upon its contiguous muscle cell. Previously, we found that the in vitro phosphorylation of soluble protein catalyzed by an endogenous protein kinase is increased in cytosolic fractions from denervated soleus muscles. This alteration occurred within several hours after the loss of some neural influence, but not as an immediate consequence of denervation (Squinto, S. P., J. A. McLane, and I. R. Held (1980) Neurosci. Lett. 20: 295–300; Squinto, S. P., J. A. McLane, and I. R. Held (1981) Neurochem. Res. 6: 203–211). In this paper, we further define the cytosolic protein substrates and demonstrate a nerve stump length-dependent phosphorylative modulation of the predominate substrate in rat soleus muscles which were denervated for 1, 3, and 6 hr and then at 6-hr intervals to 78 hr by unilaterally cutting the sciatic nerve to leave either a short (2 mm or less), intermediate (17 to 20 mm), or long (32 to 35 mm) distal nerve stump attached to the muscle. The results are compared with those obtained from sham- operated, contralateral solei and unoperated muscles. We found that the times of onset and of maximal increase of the in vitro phosphorylation of soluble cytosolic protein in denervated solei are directly related to the lengths of the distal nerve stumps; i.e., 1.4 hr/mm and 1.3 hr/mm, respectively, based upon linear regression analysis. Also, this alteration could be accounted for by an increased phosphorylation of a 56-kilodalton soluble cytosolic protein which was resolved as a minor protein-staining band after SDS slab PAGE. Although gel autoradiographs clearly showed that other soluble cytosolic proteins were also phosphorylated, approximately 80% of the incorporated 32P label was bound to the 56-kilodalton substrate. The transfer of 32PO4 from [gamma- 32P]ATP to the 56-kilodalton protein during the assay was markedly inhibited by cAMP, but was not affected by Ca2+, cGMP, or a specific inhibitor of cAMP-dependent protein kinase. The possibility that the 56- kilodalton protein substrate is the autophosphorylatable regulatory subunit of protein kinase type II is discussed. The temporal relationship of the increased phosphorylation of the 56-kilodalton protein with the denervation period and nerve stump length suggests this change is mediated by some neurotrophic regulation of skeletal muscle.